The effects of preventive aerobics mix on body composition in healthy adult women - Špirtović, Omer; Čaprić, Ilma; Stanković, Mima; Đorđević, Dušan; Murić, Benin; Kahrović, Izet; Mujanović, Rifat; Mekić, Raid; Katanić, Borko; Jelaska, Igor; Sporiš, Goran (Frontiers in Physiology, 2023)
The aim of this research was to determine the influence of a 12-week program of aerobics mix on the parameters of body composition in healthy adult women. The research has been performed in a sample of 64 women participants, and it is divided into two groups, an experimental group (E), made of 34 women participants (age 32 ± 1.8 years), and a control one (C), made of 30 women participants (age 33 ± 0.5 years). Their anthropometric and body composition were evaluated using the following respective parameters: body height, body weight, body fat percentage, muscle mass percentage, skinfold–back (KNL), skinfold–upper arm (KNN), skinfold–stomach (KNT), and skinfold–thigh (KNNK). After mix aerobics realization, among the women of the E group, there is a reduction of body mass by −2.5% and waist size by −3.39%, while muscle mass increased by 2.26%. With all skinfolds within the participants of the E group, there is a statistically important gained reduction of p < 0.05 at the final measuring, compared with the initial one (upper arm −21.10%, stomach −14.36%, back −20.58%, and upper leg −13.98%). The reduction of body mass percentage was −10.59%, and that of body mass index was −2.5%. Based on the gained results, it can be concluded that the mix program was efficient in the reduction of the subcutaneous fat tissue and visceral fat and also influential on the increase of muscle mass.